Implementation of HEMP waveforms for time-domain modeling - Mallinson, Derek; Morrow, Ivor L. (IEEE, 2018)
This paper presents recent advances in the development of HEMP waveforms with causal responses suitable for implementation in Finite Difference Time Domain models. New time-domain implementations of the HEMP environment are proposed using direct and indirect employment of the HEMP waveform. Numerical instabilities of the waveform are addressed and a new stable waveform matched to the IEC standard has been evaluated. It is concluded that the implementation of the quotient exponential model provides a stable and accurate waveform for time-domain modelling.
Keywords: Double Exponential; DEXP; FDTD; Electromagnetic Pulse; QEXP; HEMP; Time Domain; Quotient Exponential